Higher Erythrocyte n–3 PUFAs Are Associated with Decreased Blood Pressure in Middle-Aged and Elderly Chinese Adults. Issue 8 (25th June 2014) - Zeng, Fang-fang; Sun, Li-li; Liu, Yan-hua; Xu, Ying; Guan, Ke; Ling, Wen-hua; Chen, Yu-ming
Abstract: Previous studies suggested that blood fatty acids (FAs) might affect blood pressure (BP), but the findings have been inconclusive. This study evaluated the cross-sectional and prospective associations of erythrocyte FAs with BP in middle-aged and elderly Chinese individuals. Between 2008 and 2010, 1834 participants (1364 women and 470 men) aged 57 ± 5 y had baseline measurements taken of their erythrocyte FAs and BP. A total of 1477 participants (1103 women and 374 men) had their BP measured again after 3.09 ± 0.32 y (range: 2.91–3.26 y). In the cross-sectional analyses ( n = 1834), the erythrocyte saturated FA (SFA) content was positively associated with BP, whereas total cis polyunsaturated FAs (PUFAs), their subtypes cis n–3 (ω-3) PUFAs and cis n–6 (ω-6) PUFAs, and the PUFA-to-SFA ratio were inversely associated with BP (all P -trends < 0.05). The longitudinal results ( n = 1477) showed marginally inverse associations between cis n–3 PUFAs and the n–3:n–6 PUFA ratio and BP. For individual cis n–3 PUFAs, higher contents of 20:5n–3, 22:5n–3, and 22:6n–3 were significantly associated with reduced increases in SBP over time (the mean change range between quartile 4 and quartile 1 was −0.917 to −0.749 mm Hg for SBP; all P -trends < 0.01), and 20:5n–3 was inversely associated with DBP change (the mean change between quartile 4 and quartile 1 was −0.631; P -trend < 0.001). Path analyses suggested that the associations between cis n–3 PUFAs and BP might be mediated by decreasing serum triglycerides (TGs) and body mass index (BMI). Our findings revealed that a higher content of cis n–3 PUFAs (mainly very long-chain cis n–3 PUFAs) may benefit BP progress, probably mediated by decreasing serum TGs and BMI.